The role of ethics in the educational process implemented in the university space - Kapias, Michał; Polok, Grzegorz (Annales. Etyka w Życiu Gospodarczym, 2019)
Global changes around the world have demanded various transformations, including in the area of higher education. The aim of academic education is no longer to prepare people to work in particular occupations, but to create the appropriate abilities which are useful in the labor market. This kind of education must embody a multi-aspect character, because it prepares people for life-long learning. Therefore, when creating a “learning society”, one should make an effort to think of axiological dimension of scientific-technical advance. One ought to take into account the human elements of education, especially ethical issues. Practice shows that human relationships bereft of a transcendent and ethical dimension, and which focus only on financial, economic goods, on profit, the market and competition, do not bring anyone happiness. Hence there is an enormous demand in the academic community for ethical reflection, thanks to which, man is not only improved in the anthropological dimension, but also in the socio-economic aspect.